Artemis Fowl : the Arctic incident / #2 - Colfer, Eoin (Artemis Fowl, 2004)
Thirteen-year-old criminal mastermind Artemis Fowl must join forces with his nemesis, Captain Holly Short of the LEPrecon fairy police, in order to save his father--one of the few people in the world Artemis loves--who has been kidnapped by the Russian Mafiya.